Knowledge of HIV/aids and attitudes towards people living with HIV/aids (PLWHA) among undergraduate students in University Malaysia Sabah - Zulkhairul Naimbin Sidek Ahmad; Siti Fatimah Sa’at; Farrah Ilyani Che Jamalludin; Mazlinda Musa (Malaysian Journal of Medicine and Health Sciences, 2020)
Globally, HIV/AIDS has been a growing global threat and one of the major public health challenges. In Malaysia, the number of PLWH is continued to increase year by year. What is of alarming concern is that the prejudices related to HIV/AIDS still exist within the community. Stigma and discrimination towards people living with HIV have been widely documented. It has extended their impact into the workplace and this hinders HIV prevention efforts and indirectly affected the national development processes. The aim of this study was to determine the knowledge of HIV/AIDS and the attitude of PLWHA among students in Universiti Malaysia Sabah. Methods: This is a cross-sectional study with convenience sampling techniques used. Data were collected among the 300 medical students and non-medical students. Self-administered questionnaires were distributed and comprise of; sociodemographic characteristics, items assessing knowledge of HIV/AIDS and attitudes towards PLWHA. Results: The majority of respondents were female (74%) who had never encountered PLWH (76%). The mean score of knowledge and attitudes were 4.04±1.12 and 27.18±4.0, respectively. Year 1 male students were found to have more comprehensive knowledge of HIV/AIDS. They were also having a more positive attitude toward PLWH as compared to female students. Conclusion: Stigma and discrimination associated with HIV/AIDS are the most challenges issues experienced by people suffering from the disease and it has been recognized. It is regarded as a serious threat to the fundamental rights of all infected people who are affected by or associated with this disease. This study highlights the need for better education programs on HIV/AIDS at the undergraduate level in order to increase knowledge of HIV/ AIDS and shape the positive attitude toward PLWH.